AICAR, an AMP-Activated Protein Kinase Activator, Ameliorates Acute Pancreatitis-Associated Liver Injury Partially Through Nrf2-Mediated Antioxidant Effects and Inhibition of NLRP3 Inflammasome Activation - Kong, Lijun; Zhang, Hewei; Lu, Chaosheng; Shi, Keqing; Huang, Hongjian; Zheng, Yushu; Wang, Yongqiang; Wang, Dan; Wang, Hongwei; Huang, Wei (Frontiers in Pharmacology, 2021)
Acute pancreatitis (AP) is a highly fatal acute inflammation and is often accompanied by multiple organ dysfunction syndrome (MODS). The liver, one of the most vulnerable extrapancreatic organs in AP, is the major organ involved in the evolution of the disease and correlates strongly with the occurrence of MODS. However, the etiology of pancreatitis-associated liver injury (PALI) has not been clarified and currently lacks an effective treatment. 5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR) is a cell permeable nucleoside with pleiotropic effects on anti-inflammatory and antioxidant stress that binds with adenosine monophosphate protein kinase (AMPK) and induces AMPK activation. However, the role of AICAR in PALI remains elusive. Here, we show that activation of AMPK by AICAR, a direct AMPK agonist, significantly ameliorates sodium taurocholate-induced PALI in rats, whereas treatment of PALI rats with the AMPK antagonist Compound C profoundly exacerbates the degree of liver injury, suggesting that hepatic AMPK activation exerts an essential protective role in PALI. Mechanistically, AICAR induces AMPK activation, which in turn activates nuclear factor erythroid 2-related factor 2(Nrf2) -regulated hepatic antioxidant capacity and inhibits NLRP3 inflammasome-mediated pyrolysis, protecting rats from sodium taurocholate-induced PALI. Nrf2 deficiency strikingly weakens the beneficial effects of AICAR on alleviation of liver injury, oxidative stress and NLRP3 inflammasome activation in L-arginine-induced PALI mice. Thus, AICAR protects against PALI in rodents by triggering AMPK, which is mediated at least in part by Nrf2-modulated antioxidant effects and NLRP3 inflammasome activation.